Bank resolution and public backstop in an asymmetric banking union - Anatoli Segura; Sergio Vicente (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
This paper characterizes the optimal banking union with endogenous participation in a two-country economy in which domestic bank failures may be contemporaneous to sovereign crises, giving rise to risk-sharing motives to mutualize the funding of bail-outs. Raising public funds to conduct a bail-out entails the deadweight loss of distortionary taxation. Bank bail-ins create disruption costs in the economy. When country asymmetry is large, resolution policies exhibit reduced contributions to the public backstop and forbearance in early bank intervention in the fiscally stronger country, facilitating bail-outs in this country.
Keywords: G01; G21; G28; 330; banking union; bail-in; bailout; public backstop; mechanism design